2001
DOI: 10.1089/105072501750302868
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Oral Radiographic Contrast Agents in the Management of Hyperthyroidism

Abstract: Oral iodinated radiographic contrast agents such as ipodate and iopanoic acid form an important part of the armamentarium used to treat hyperthyroidism. They rapidly and dramatically reduce serum triiodothyronine (T3) levels by inhibiting conversion of thyroxine (T4) to T3 in the periphery and by blocking secretion from the thyroid. Potential risks from the large iodine load resulting from their use limit their widespread applicability. In addition, they are ineffective when used alone on a long-term basis. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…1CTP, the marker of bone resorption, has convincingly been shown to correlate to free T 4 and T 3 concentrations [27, 28]. We found that in the entire group of patients, the serum levels of free T 4 and 1CTP were decreased 1 year after hemithyroidectomy.…”
Section: Discussionsupporting
confidence: 52%
“…1CTP, the marker of bone resorption, has convincingly been shown to correlate to free T 4 and T 3 concentrations [27, 28]. We found that in the entire group of patients, the serum levels of free T 4 and 1CTP were decreased 1 year after hemithyroidectomy.…”
Section: Discussionsupporting
confidence: 52%
“…The use of oral radiographic contrast agents like IOP may be useful in the treatment of thyrotoxicosis before surgery, in neonatal hyperthyroidism and in massive L-T 4 ingestion, or when other antithyroid drugs are contraindicated (20). In the present study, the period of treatment with IOP or SSKI in association with anti-thyroid drugs was sufficient for all to achieve clinical euthyroidism before surgery.…”
Section: Discussionmentioning
confidence: 60%
“…Serum T 3 levels can decrease 36% to 77% within 6 to 12 hours and normalize within 2 to 5 days. 7 In contrast, thyroid hormone levels take 6 to 8 weeks to normalize with thionamides, such as propylthiouracil and methimazole. 9 After 24 hours of treatment, T 3 levels decreased by 58% with ipodate (1 g/d) compared with 23% with propylthiouracil (600 mg/d) in Graves disease patients.…”
Section: Discussionmentioning
confidence: 99%